O-029 Self-expanding stent versus drug-eluting balloon-expandable stent for intracranial arterial stenosis. (22nd July 2018) - Sambursky, J; Padalia, A; Gandhi, R; Bellew, M; Hellinger, F
Abstract : Objective: The purpose of this study is to compare the outcomes of percutaneous transluminal angioplasty and stenting (PTAS) for intracranial arterial stenosis (ICAS) using self-expanding (SE) stents, bare metal balloon expandable (BMBE) stents, and (anti-mitogenic) drug-eluting balloon expandable (DEBE) stents. Methods: We retrospectively reviewed all 195 cases of intracranial stenting for atherosclerotic stenosis performed by a single operator at a single institution from August 1998 to August 2017. Rates of residual stenosis, in-stent restenosis (ISRS) and adverse events were calculated for patients treated with each stent type. Results: The results of the analysis for the entire cohort will be presented. Currently we report the results of our analysis for 60 patients for whom all desired data points were available. Mean pre-procedural stenosis rate was 84%. Of these, 42 were treated with SE (Wingspan) stents and 18 were treated with DEBE stents. The mean angiographic follow-up period was 8.2±4.5 months. The rate of significant residual stenosis immediately after PTAS (≥30%) was higher in the SE group (42.5%, 17 of 40) than the DEBE group (11.1%, 2 of 18; p=0.02). The rate of significant in-stent restenosis (≥50%) at angiographic follow-up was also higher in the SE group (47.5%, 19 of 40) than the DEBE group (16.6%, 3 of 18; p=0.03). The incidence of an ischemic event in the same distribution as the stent was higher in the SE group (37.5%, 15 of 40) than the DEBE group (11.1%, 2 of 18; p=0.039). The incidence of stroke or death within 30 days of PTAS was higher in the SE group (7.1%, 2 of 42 died from ICH, 1 of 42 from ischemic stroke) than the DEBE group (0%, 0 of 18; p=0.25). The incidence of TIA, stroke, or death within 30 days of PTAS was also higher in the SE group (9.5%, 4 of 42) than the DEBE group (0%, 0 of 18; p=0.18). Conclusion: In regards to post-operative residual stenosis, in-stent restenosis, periprocedural complications, and ischemic events within the same distribution as the affected artery, DEBE stents were more effective than SE stents. Disclosures: J. Sambursky: None. A. Padalia: None. R. Gandhi: None. M. Bellew: None. F. Hellinger: None.